IMPLEMENTASI PROGRAM PELAYANAN IZIN DI TEMPAT DENGAN HANGAT, AMANAH, TRANSPARAN DAN INOVATIF (PELITA HATI) DALAM PEMBUATAN SURAT IZIN USAHA DI KABUPATEN PROBOLINGGO - Verto Septiandika; Alvia Sholeha (Universitas Halu Oleo, 2022)
Currently, services in the licensing administration sector are the types of services that are quite in demand such as Building Construction Permits, Transportation Uzaha Permits, Fisheries Business Permits, Plantation Business Permits, Industrial Business Permits, more specifically regarding Trading Business Permits. Through the Investment Coordinating Board (BKPM) the Probolinggo Regency created an innovative on-site permit service program, namely PELITA HATI which aims to assist the community in making business licenses. This study aims to describe the Implementation of a Warm, Trustworthy, Transparent and Innovative Service Permit Service Program (Pelita Hati) in Making Business Licenses in Probolinggo Regency. The research method used is descriptive qualitative. The selection of informants was chosen deliberately who was considered to understand the problem, took data from relevant sources according to the theme raised, so as to produce reliable data and determine the accuracy of the research results. The results showed that the implementation of the Pelita Hati program in making business licenses in Probolinggo Regency was running well and optimally.